History Of Pre-School Educational Institutions In Uzbekistan In 1946-1970 - Tishabaeva Irodakhon Rasulovna (Zien Journals, 2024)
This article describes the measures taken by the Soviet authorities in Uzbekistan in the field of preschool education on the basis of scientific, historical literature and sources. Also, the study included preschool education, children's attendance and demographic indicators
Keywords: preface; archival sources; management mechanism; non-governmental